Syndrome De Guillain-Barré Chez L’enfant Dans Un Contexte A Ressources Limitées : A Propos De Deux Observations Au CHU Sylvanus Olympio De Lomé - TOGO - Akolly, Dae.; Guedenon, Km.; Tsolenyanu, E.; Takassi, E.; Fiawoo, M.; Atakouma, Y. (European Scientific Journal, ESJ, 2016)
Guillain-Barré syndrome is rare in children. With polyvalent immunoglobulins the management and prognosis has been significantly improved with complete recovery rate exceeding 80%. We report the cases of two children who completely recovered after Guillain-Barré syndrome in the absence of immune globulin. He was a 12 year old daughter and an infant of 17 months male who presented a progressive ascending motor deficit, dysphonia with difficulty swallowing, difficulty breathing, areflexia. A albumino-cytological dissociation was found in the study of cerebrospinal fluid in both cases. Electromyography in the girl had confirmed a axono-form myelin. Retroviral serology was negative in both cases. Other serology (Campylobacter jejuni, Cytomegalovirus, Epstein Barr, ZIKA), the dosage of anti-ganglioside antibodies and brain imaging had not been made. The immunoglobulins are not available in our work context, we conducted a symptomatic management. Complete healing was achieved with a 4-month decline.